Pengaruh Pengetahuan Zakat dan Citra Lembaga Terhadap Minat Muzakki dalam Membayar Zakat Fitrah - Ubay Haki (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The scientific article has three discussion variables, this variable is zakat knowledge, image of the institution, and interest in muzakki. This paper is the result of a study aiming to want to now influence of two variables, that is the variable, of zakat knowledge on muzakki’s interest, variable image of the institution towards muzakki’s interest, and together two variables zakat knowledge and institutional image towards muzakki’s interest in paying zakat at BAZNAS Banten Province through the Bina Bangsa University Zakat Collecting Unit (UPZ). As for method of writing this scientific article using quantitative research methods the technique used in obtaining samples is with saturated samples, as revealed in Sugiyono’s theory, because the population does not reach 100 people, there only 82 people who actively pay zakat fitrah every year to Banten Provincial BAZNAS through UPZ Bina Bangsa University. in using data collecting questionnaires in the form of a statement list which distributed to respondent, than counduct interviews and documentation, and likert scale measurement using SPSS aids. By looking at research and statistical calculations the linear regression equation Y= 0,005 + 0,680 X1 + 0,523 X2 and correlation coefficient (R) = 0,930 while the coefficient of determination (R2 x 100%) = 88%, which means that the ability of the independent variable in explaining the dependent variable of 86.5%, while the remaining 13.5% is influenced by other aspects not described in this scientific article. Than it can be concluded apparently there is an influence between the knowledge of zakat on muzakki’s interest in paying zakat fitrah of 84.3%, there is also an influence of the institution image on muzakki’s interest in paying zakat fitrah of 82.3%, and there is a simultaneous influence between the knowledge of zakat and the image of the institution towards muzakki’s interest in paying zakat fitrah 86.5%, as well as the rest about 13.5% was influenced by other aspects not explained in this scientific article.